1977
DOI: 10.4141/cjps77-064
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Forage Maturity to Digestibility and Animal Gain When Silage Is Untreated or Treated With Formic Acid

Abstract: Cer-osn, F. W. 1977. Relarionship

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1996
1996

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Composition of the three silages is shown in Thomas et al (1988) Calder (1977) and Martinsson (1990), DM digestibility measured in vitro declined with forage maturity. Surprisingly, NDF and ADF increased between silages E and M and then declined between silages M and L. However, lignification followed the expected pattern, with 5.8% in silage E, 6.5%0 silage M and 9.lo/o in silage L. A similar observation was made by Seoane et al (1991), who suggested that the water stress and temperature prevailing during the week before harvest could affect ADF and NDF values more than the age of the plant.…”
Section: Resultsmentioning
confidence: 97%
“…Composition of the three silages is shown in Thomas et al (1988) Calder (1977) and Martinsson (1990), DM digestibility measured in vitro declined with forage maturity. Surprisingly, NDF and ADF increased between silages E and M and then declined between silages M and L. However, lignification followed the expected pattern, with 5.8% in silage E, 6.5%0 silage M and 9.lo/o in silage L. A similar observation was made by Seoane et al (1991), who suggested that the water stress and temperature prevailing during the week before harvest could affect ADF and NDF values more than the age of the plant.…”
Section: Resultsmentioning
confidence: 97%
“…Plant Sci. 622 89-94 (Jan. 1982) bloom stage, which converted to animal gain per hectare of 465 kg for vegetative stage and 275 kg at bloom stage (Calder 1977). When forage is not of the highest possible quality, feeding ground barley with the silage is usually beneficial.…”
mentioning
confidence: 99%